Microsphere, noble metal supported catalyst, silicon dioxide microsphere, and preparation method and application of microsphere, noble metal supported catalyst and silicon dioxide microsphere
By mixing phenol and alkaline catalysts in the solvent and adding silicates at a specific time to form phenolic resin/silica composite particles, the carbon microspheres that are difficult to prepare large mesoporous structures and stable spherical morphology in the prior art are solved, and their high-performance applications in catalyst support and supercapacitor materials are achieved.
Patent Information
- Application Number
- CN202311082468.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-25
- Publication Date
- 2025-02-28
AI Technical Summary
The prior art is difficult to prepare solid mesoporous carbon microspheres and silica microspheres with large mesoporous structures and stable spherical morphology, limiting their application in catalyst support and supercapacitor materials.
By mixing phenol and alkaline catalyst in the solvent, adding aldehydes and reacting until cloudy, and then adding silicates at a specific time to form phenolic resin/silica composite particles, the silica template is carbonized and removed to obtain solid mesoporous carbon microspheres.
The prepared carbon microspheres have large mesoporous structure and stable spherical morphology, and they exhibit good electrochemical properties and catalytic effects as catalyst support and supercapacitor materials.
Smart Images

Figure CN119524748A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of silicon and carbon materials, and in particular to solid mesoporous carbon microspheres, noble metal-loaded catalysts and silicon dioxide microspheres, as well as preparation methods and applications thereof. Background Art
[0002] The increasingly severe global problems brought about by resource consumption and environmental pollution, including rising temperatures, destruction of vegetation, and impacts on animal diversity, have seriously affected human survival. The development of renewable, low-carbon energy is essential for humans to achieve green and sustainable development. New energy storage devices based on renewable energy are increasingly gaining attention. Electrode materials are an important component of energy storage devices and have a significant impact on their performance. Porous carbon microspheres are favored by everyone for their rich pores and morphological structures and stable physical and chemical properties. The development of porous carbon microsphere electrode materials with high electrochemical properties is an important way to obtain high-performance energy storage devices, and it is also a technical content that technicians need to continuously break through in the future. Therefore, the controllable preparation and structural regulation of porous carbon microspheres based on molecular level design and their influence on electrochemical performance have become a hot topic in this field.
[0003] Porous carbon microspheres have solid, hollow, core-shell and other structures in morphology. Carbon microspheres with different structures have different characteristics. In comparison, solid carbon microspheres have a uniform morphology and are a commonly used electrode material. From the classification of pore structure, there are micropores, mesopores and macropores. The regulation of pore structure can make porous carbon microspheres meet the application requirements in different fields, such as applying microporous carbon microspheres to adsorption and energy storage, applying mesoporous carbon microspheres to energy storage, and applying macroporous carbon microspheres to material storage and transportation. For example, Liu et al. (Angew Chem Int Ed Engl, 2011, 50(26): 5947-5951) used resorcinol as a monomer and adopted the expanded The monodisperse polymer microspheres and carbon microspheres were prepared by this method. The particle size of the microspheres can be effectively controlled by adjusting the ammonia concentration, resorcinol content, water-to-alcohol ratio, etc. Tanaka et al. (The Journal of Physical Chemistry C, 2012, 116(51): 26791-26799) used an improved By adjusting the concentration of ammonia water, a series of carbon microspheres with a size of 220 to 1140 nm were prepared, showing good supercapacitor performance. However, these methods can only produce solid microporous carbon microspheres. The preparation of mesoporous carbon microspheres still requires the assistance of surfactants. For example, Professor Zhao's team at Fudan University (Angew Chem Int Ed Engl, 2010, 49 (43): 7987-7991) developed a method for low-concentration hydrothermal synthesis of mesoporous carbon microspheres (O-MCS) using a triblock copolymer (Pluronic F127) as a soft template and phenolic resin as a carbon precursor. By simply adjusting the concentration of the reactants, the particle size of the obtained carbon microspheres can be easily adjusted between 20 nm and 140 nm. Similarly, by changing the concentration of F127, a similar hydrothermal process can be used to obtain ordered mesoporous carbons (MCNs) of different structures. When the concentration of F127 is about 12wt.% and 9wt.%, rod-shaped and worm-shaped mesoporous carbon nanoparticles can be obtained. When the concentration is further reduced to 6wt.%, spherical carbon nanoparticles can be obtained. The size of the carbon spheres can be adjusted by further reducing the concentration of F127 (Journal of Colloid and Interface Science, 2012, 377 (1): 169-175). It is still a challenge to obtain solid mesoporous carbon microspheres without surfactant. Carbon microspheres with regular spherical morphology and large mesopore size show good application prospects, such as for catalyst supports, electrode materials, adsorption materials, etc.
[0004] Precious metal catalysts have shown outstanding performance in chemical reactions, drug synthesis, automobile exhaust treatment, LED chips, circuit boards, etc., and are widely used. However, they have small contact areas, low utilization rates, and are difficult to recycle. Loading them on carriers can effectively improve the catalytic effect. How to improve their performance through carrier design is of great significance.
[0005] Silicon dioxide (SiO2) is a non-toxic, odorless, and non-polluting inorganic material that can be used as a filler and reinforcing agent for rubber, coatings, and plastics. Existing silicon dioxide is mainly a microporous structure, which limits its application in electrode materials, electronic appliances, and aerospace fields. How to prepare mesoporous solid nano-silica with regular spherical morphology by a simple method has important practical application value. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a method for preparing microspheres (solid mesoporous carbon microspheres) and their derivatives, such as noble metal-loaded catalysts and silicon dioxide microspheres, and their applications. The method is simple to prepare, the carbon material structure is easy to control, and the prepared carbon microspheres have a large mesoporous structure and a stable spherical morphology, which can be used to prepare noble metal-loaded catalysts and have good performance as supercapacitor materials. The silicon microspheres prepared based on the method have a regular spherical morphology, low metal ion content, and rich pore structure.
[0007] In order to solve the above technical problems, the present invention provides a method for preparing microspheres, comprising the following steps:
[0008] S1, mixing phenol and an alkaline catalyst in a solvent to obtain a reaction solution;
[0009] S2, adding aldehyde to the reaction solution, reacting until turbidity appears, and continuing the reaction for 0 to 90 minutes to obtain a turbid solution;
[0010] S3, adding silicate to the turbid liquid, and continuing the reaction for 1 to 48 hours;
[0011] S4, separating and obtaining phenolic resin / silicon dioxide composite particles;
[0012] S5, carbonizing the phenolic resin / silicon dioxide composite particles and removing silicon dioxide to obtain solid mesoporous carbon microspheres.
[0013] Furthermore, the phenol is selected from at least one of resorcinol and 3-aminophenol.
[0014] Furthermore, the alkaline catalyst is selected from at least one of ammonia water, ethylenediamine, ethylamine, diethylamine, triethylamine, hexamethylenetetramine, sodium hydroxide, potassium hydroxide, barium hydroxide and magnesium hydroxide.
[0015] Furthermore, the solvent is selected from at least one of water, ethanol, methanol, acetone, tetrahydrofuran, methane and chloroform.
[0016] Furthermore, the aldehyde is selected from formaldehyde or paraformaldehyde.
[0017] Furthermore, the silicate is selected from at least one of tetraethyl silicate, tetrapropoxysilane, tetraisopropyl orthosilicate, and tetrabutyl silicate.
[0018] Furthermore, the silicate is added into the turbid solution 10 to 40 minutes after the reaction solution starts to become turbid.
[0019] Furthermore, the molar ratio of the phenol to the aldehyde is 1:(1-10).
[0020] Furthermore, the molar ratio of the alkaline catalyst to phenol is (1-30):1.
[0021] Further provided is a microsphere prepared by the above preparation method.
[0022] Further provided is a noble metal-loaded catalyst, wherein the microspheres prepared by the above-mentioned preparation method are loaded with noble metal compounds.
[0023] Furthermore, the precious metal compound is selected from at least one of rhodium trichloride, gold trichloride, gold(II) chloride, palladium chloride, chloroauric acid, chloroplatinic acid, potassium hexachloroplatinate, sodium hexachloroplatinate, platinum tetrachloride, platinum acetylacetonate, palladium nitrate, palladium acetate, and tetrachloropalladium ammonium.
[0024] Further provided is a silica microsphere, which is obtained by removing the phenolic resin inside the microsphere from the microsphere prepared by the above preparation method.
[0025] Furthermore, the present invention provides the use of the aforementioned microspheres in preparing energy storage devices, adsorbents, catalyst carriers, and drug carriers.
[0026] Wherein, the energy storage device is one of a supercapacitor, a lithium-ion battery, a fuel cell, and an air battery.
[0027] Further provided is the use of the aforementioned silica microspheres in preparing battery separators, drug carriers, toothpaste fillers, and silica gel reinforcing agents.
[0028] The beneficial effects of the present invention are as follows: the carbon material prepared by the preparation method of the present invention has a solid spherical morphology and a mesoporous structure, and the mesopore diameter is large. As a supercapacitor electrode material, it shows good electrochemical performance. The use of the carbon material to prepare a noble metal-loaded catalyst can reduce the amount of noble metals and effectively improve the use efficiency of the catalyst. The silica microspheres prepared by the present invention have a regular spherical morphology and a solid mesoporous structure, and the preparation method is simple. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a SEM image of the carbon microspheres prepared in Example 1 of the specific embodiment of the present invention;
[0030] Figure 2 TEM image of carbon microspheres prepared in Example 1 of the specific embodiment of the present invention;
[0031] Figure 3 This is a TEM image of the carbon microspheres prepared in Comparative Example 1 in a specific embodiment of the present invention. DETAILED DESCRIPTION
[0032] In order to explain the technical content, achieved objectives and effects of the present invention in detail, the following is an explanation in combination with the implementation modes and the accompanying drawings.
[0033] In the present invention, the initial hydrolysis time of silicate is delayed by condensation control to achieve condensation matching with resorcinol. Specifically, the initial hydrolysis time of silicate is extended until resorcinol and formaldehyde condense to form particles of a certain size and quantity, so that the condensation of resorcinol / formaldehyde and the condensation of silicate reach the best match. In this case, the particles formed by their respective condensation are assembled together to form composite particles through hydrogen bonding. Among them, the silica produced by the hydrolysis of silicate is used as a pore structure template, and after carbonization and removal of the silica template, a solid structure mesoporous carbon microsphere material is formed. Solid silica microspheres can be obtained by further removing the phenolic resin template.
[0034] Specifically, the present invention provides a method for preparing microspheres, which comprises: firstly reacting phenol and aldehyde in an alkaline solution until the solution becomes turbid by precise control of hydrolysis and condensation, then adding silicate at a specific time, so that phenolic resin particles produced by the condensation reaction of phenol and aldehyde and silica particles produced by hydrolysis and condensation of silicate are co-assembled to form phenolic resin / silicon dioxide composite particles, and then obtaining solid mesoporous carbon microspheres after further carbonization and removal of silica, comprising the following steps:
[0035] S1, mixing phenol and an alkaline catalyst in a solvent to obtain a reaction solution;
[0036] S2, adding aldehyde to the reaction solution, reacting until turbidity appears, and continuing the reaction for 0 to 90 minutes to obtain a turbid solution;
[0037] S3, adding silicate to the turbid liquid, and continuing the reaction for 1 to 48 hours;
[0038] S4, separating and obtaining phenolic resin / silicon dioxide composite particles;
[0039] S5, carbonizing the phenolic resin / silicon dioxide composite particles and removing silicon dioxide to obtain solid mesoporous carbon microspheres.
[0040] Specifically, the silicate such as tetraethyl silicate, tetrapropoxysilane, tetraisopropyl orthosilicate, tetrabutyl silicate, under the action of alkaline catalyst, has a rapid hydrolysis condensation rate in solvent, can quickly form silica microspheres, is an effective method for preparing monodisperse silica. The condensation rate of phenol and aldehyde is relatively slow, specifically, the phenol such as at least one of resorcinol and 3-aminophenol, the aldehyde such as formaldehyde or paraformaldehyde, the reaction between them is relatively slow. Taking tetraethyl silicate and resorcinol / formaldehyde as examples, if they are added to the reaction system (containing a system of solvent and alkaline catalyst) at the same time, tetraethyl silicate will hydrolyze and condense rapidly to form silica, and become the core, after which the phenolic resin formed by the condensation of resorcinol and formaldehyde is coated on the silica surface, carbonized and removed silica, can only obtain hollow carbon microspheres (Comparative Example 1) with microporous structure. Therefore, in order to obtain the mesoporous carbon microsphere material of the present invention, we first put phenol and aldehyde into the reaction system to make them preferentially condense to form initial phenolic resin particles, and then add silicate at the right time to make them achieve a good condensation match, and make the silica particles produced by the hydrolysis and condensation of silicate co-assemble with the phenolic resin particles to form composite microspheres.
[0041] Further, the alkaline catalyst is one or a combination of two or more of ammonia water, ethylenediamine, ethylamine, diethylamine, triethylamine, hexamethylenetetramine, sodium hydroxide, potassium hydroxide, barium hydroxide, and magnesium hydroxide, preferably an ammonia / amine catalyst, and the ammonia / amine catalyst is ammonia water, ethylenediamine, ethylamine, diethylamine, triethylamine, or hexamethylenetetramine, more preferably ammonia water, diethylamine, or hexamethylenetetramine. The solvent is one or more of water, ethanol, methanol, acetone, tetrahydrofuran, methane, and chloroform, preferably water, ethanol, or methanol, or a combination thereof.
[0042] Accurately controlling the degree of condensation of phenol and aldehyde and adding silicate at a specific time are the keys to obtaining the solid mesoporous carbon microsphere material of the present invention. Specifically, the present invention controls the condensation reaction of phenol and aldehyde until turbidity, and after the initial particles of phenolic resin appear, silicate is added after continuing the reaction for 0 to 90 minutes. At this time, the silica particles produced by the condensation and hydrolysis of silicate will be assembled with the phenolic resin particles to form composite microspheres, and solid mesoporous carbon microspheres are obtained after carbonization and removal of silica. The addition time of the silicate can be further preferably 10 to 40 minutes after the phenol and aldehyde react to turbidity. Aldehyde and phenol react at a higher molar ratio to ensure the stability of the size of the prepared composite microspheres. The molar ratio of phenol to aldehyde is preferably 1: (1 to 10), more preferably 1: (1.5 to 3). The appropriate molar ratio of phenol to aldehyde can not only make the resin have sufficient crosslinking degree to form stable microspheres, but also reduce the amount of aldehyde used and reduce the content of unreacted aldehyde in the system. Furthermore, the concentration of the phenol in the solution is 0.3-100 mg / mL, and the size of the microspheres can be controlled by the amount of phenol. Furthermore, the alkaline catalyst can also control the size and reaction rate of the microspheres, and the molar ratio of the alkaline catalyst to the phenol is (1-30):1.
[0043] A silicon dioxide microsphere, the microsphere (phenolic resin / silicon dioxide composite particle) prepared by the above-mentioned preparation method is obtained by removing the phenolic resin inside it. The method for removing the phenolic resin inside it can be a physical method or a chemical method, such as dissolving the phenolic resin with a solvent, or removing the phenolic resin by carbonization and burning in the air. The metal ion content of the silicon dioxide microsphere can reach below 200ppm, and is further preferably below 100ppm, which can be used as an electronic grade.
[0044] The large mesopore size provides a guarantee for the application of the prepared carbon material in electrode materials. The carbon material can be applied to energy storage devices such as supercapacitors, lithium-ion batteries, fuel cells, and air batteries, and can also be used as an adsorbent, catalyst carrier, drug carrier, etc. The prepared silicon dioxide has a regular spherical morphology, low metal ion content, rich pore structure, and large mesopore size, and can be used in battery separators, drug carriers, toothpaste fillers, silicone reinforcing agents, etc.
[0045] A noble metal-loaded catalyst, wherein the microspheres prepared by the above-mentioned preparation method are loaded with a noble metal compound. Specifically, based on the solid mesoporous carbon microspheres, the solid mesoporous carbon microspheres are dispersed in a solvent, and the noble metal compound is added and stirred to disperse and adsorb, and the noble metal-loaded catalyst is obtained after filtering, drying, and high-temperature carbonization. The noble metal-loaded catalyst has a high specific surface area and a large mesopore size, and can play a good catalytic effect.
[0046] Preferably, the precious metal compound is selected from at least one of rhodium trichloride, gold trichloride, gold(II) chloride, palladium chloride, chloroauric acid, chloroplatinic acid, potassium hexachloroplatinate, sodium hexachloroplatinate, platinum tetrachloride, platinum acetylacetonate, palladium nitrate, palladium acetate, and tetrachloropalladium ammonium.
[0047] Example 1
[0048] A method for preparing microspheres comprises the following steps:
[0049] S1. Add ammonia water (25%) to a solvent consisting of water and ethanol, add resorcinol, and stir evenly;
[0050] S2, add formaldehyde (37% aqueous solution) to the reaction solution of S1, react until turbidity appears, and continue the reaction for 20 minutes;
[0051] S3, adding ethyl silicate to the reaction solution of S2, and continuing the reaction for 24 hours;
[0052] S4, after separation, phenolic resin / silicon dioxide composite microspheres are obtained;
[0053] S5, phenolic resin / silica composite microspheres were carbonized at 700 °C for 4 h under nitrogen protection, and the silica was removed by hydrofluoric acid to obtain solid mesoporous carbon microspheres C1 (such as Figure 1 and 2 shown);
[0054] The volume ratio of water to alcohol is 1:7;
[0055] The molar ratio of ammonia water to resorcinol is 11:1;
[0056] The concentration of resorcinol in the solution is 5 mg / mL;
[0057] The molar ratio of formaldehyde to resorcinol is 2:1;
[0058] The molar ratio of tetraethyl silicate to resorcinol is 3.4:1;
[0059] After testing, the BET of carbon microsphere C1 is 790.7m 2 ·g -1 , mesopore diameter is 12nm.
[0060] Preparation of silica microspheres: The phenolic resin / silicon dioxide composite microspheres obtained in S4 were carbonized in air at 600°C for 2 h to remove the phenolic resin and obtain silica microspheres. The total metal ion content (iron, aluminum, copper, sodium, potassium) was 45 ppm.
[0061] Preparation of platinum-loaded carbon microspheres: 1.5 g of solid mesoporous carbon microsphere material C1 was dispersed in 100 mL of ethanol solution, followed by the addition of 0.06 g of chloroplatinic acid, and after stirring, ultrasonic treatment was used to disperse and adsorb it. After filtration and drying, the carbonization was then carried out at 800 °C for 2 h under a nitrogen atmosphere to obtain a platinum-loaded carbon microsphere catalyst.
[0062] Comparative Example 1
[0063] A method for preparing microspheres comprises the following steps:
[0064] S1. Add ammonia water (25%) to a solvent consisting of water and ethanol, add resorcinol, and stir evenly;
[0065] S2, adding formaldehyde (37% aqueous solution) and tetraethyl silicate to the reaction solution of S1, and reacting for 24 hours;
[0066] S3, microspheres are obtained after separation;
[0067] S4, the microspheres were carbonized at 700 ° C for 4 h, and the silicon dioxide was removed by hydrofluoric acid to obtain the hollow carbon material C2 (such as Figure 3 shown).
[0068] The volume ratio of water to alcohol is 1:7;
[0069] The molar ratio of ammonia water to resorcinol is 11:1;
[0070] The concentration of resorcinol in the solution is 5 mg / mL;
[0071] The molar ratio of formaldehyde to resorcinol is 2:1;
[0072] The molar ratio of tetraethyl silicate to resorcinol is 3.4:1;
[0073] After testing, the BET of carbon microspheres is 514m 2 ·g -1 , pore diameter is about 0.7nm.
[0074] Preparation of platinum-loaded carbon microspheres: 1.5 g of carbon microsphere material C2 was dispersed in 100 mL of ethanol solution, followed by the addition of 0.06 g of chloroplatinic acid, and after stirring, ultrasonic treatment was used to disperse and adsorb it. After filtration and drying, the carbonization was then carried out at 800 °C for 2 h under a nitrogen atmosphere to obtain a platinum-loaded carbon microsphere catalyst.
[0075] Example 2
[0076] 1) Add ammonia water (25%) to a solvent consisting of water and ethanol, add resorcinol, and stir evenly;
[0077] S2, add formaldehyde (37% aqueous solution) to the reaction solution of S1, react until turbidity appears, and continue the reaction for 30 minutes;
[0078] S3, adding ethyl silicate to the reaction solution of S2, and continuing the reaction for 24 hours;
[0079] S4, after separation, phenolic resin / silicon dioxide composite microspheres are obtained;
[0080] S5, phenolic resin / silica composite microspheres were carbonized at 700°C for 4 h and silica was removed with hydrofluoric acid to obtain solid mesoporous carbon microspheres C3.
[0081] The volume ratio of water to alcohol is 1:7;
[0082] The molar ratio of ammonia water to resorcinol is 11:1;
[0083] The concentration of resorcinol in the solution is 5 mg / mL;
[0084] The molar ratio of formaldehyde to resorcinol is 2:1;
[0085] The molar ratio of tetraethyl silicate to resorcinol is 3.4:1;
[0086] After testing, the BET of carbon microspheres is 822m 2 ·g -1 , mesopore diameter is 13nm.
[0087] Preparation of silica microspheres: The phenolic resin / silicon dioxide composite microspheres obtained in S4 were carbonized in air at 500°C for 2 h to remove the phenolic resin and obtain silica microspheres. The total metal ion content (iron, aluminum, copper, sodium, potassium) was 42 ppm.
[0088] Preparation of palladium-loaded carbon microspheres: 2 g of solid mesoporous carbon microsphere material C3 was dispersed in 100 mL of ethanol solution, followed by the addition of 2 mL of palladium chloride ethanol solution (concentration of 0.02 g / mL), and after stirring, ultrasonic treatment was used to disperse and adsorb it. After filtration and drying, the palladium-loaded carbon microsphere catalyst was obtained after carbonization at 800 °C for 2 h under a nitrogen atmosphere.
[0089] Example 3
[0090] A method for preparing microspheres comprises the following steps:
[0091] S1. Add ammonia water (25%) to a solvent consisting of water and ethanol, add resorcinol, and stir evenly;
[0092] S2, add formaldehyde (37% aqueous solution) to the reaction solution of S1, react until turbidity appears, and continue the reaction for 20 minutes;
[0093] S3, adding ethyl silicate and tetrapropoxysilane (molar ratio of 1:1) to the reaction solution of S2, and continuing the reaction for 24 hours;
[0094] S4, after separation, phenolic resin / silicon dioxide composite microspheres are obtained;
[0095] S5, phenolic resin / silica composite microspheres were carbonized at 700°C for 4 h and silica was removed with hydrofluoric acid to obtain solid mesoporous carbon microspheres C4.
[0096] The volume ratio of water to alcohol is 1:7;
[0097] The molar ratio of ammonia water to resorcinol is 11:1;
[0098] The concentration of resorcinol in the solution is 5 mg / mL;
[0099] The molar ratio of formaldehyde to resorcinol is 2:1;
[0100] The molar ratio of ethyl silicate + tetrapropoxysilane to resorcinol is 3.4:1;
[0101] After testing, the BET of carbon microspheres is 886m 2 ·g -1 , mesopore diameter is 15nm.
[0102] Preparation of silica microspheres: The phenolic resin / silicon dioxide composite microspheres obtained in S4 were carbonized in air at 500°C for 2 h to remove the phenolic resin and obtain silica microspheres. The total metal ion content (iron, aluminum, copper, sodium, potassium) was 46 ppm.
[0103] Preparation of gold-loaded carbon microspheres: 1.5 g of solid mesoporous carbon microsphere material C4 was dispersed in 100 mL of ethanol solution, followed by the addition of 6 mL of chloroauric acid aqueous solution (concentration of 0.01 g / mL), and after stirring, ultrasonic treatment was used to disperse and adsorb it. After filtration and drying, the gold-loaded carbon microsphere catalyst was obtained after carbonization at 800 °C for 2 h under a nitrogen atmosphere.
[0104] Test example
[0105] The microspheres prepared in Examples 1 to 3 and Comparative Example 1 were subjected to catalytic performance tests and supercapacitor performance tests, and the results are shown in Table 1.
[0106] Catalytic performance test: 0.004 g of the prepared supported carbon microsphere catalyst was added with 0.2 mL of isopropanol, 0.77 mL of water and 0.032 mL of 5 wt.% Nafion solution. After ultrasonic dispersion, a uniform slurry was obtained. 10 μL of the slurry was added dropwise to a 0.196 cm 2The surface of the glassy carbon electrode was dried in a fume hood for 2 h to obtain a loading of 0.2 mg / cm 2 The working electrode was used, and oxygen was passed at a flow rate of 50 mL / min for 30 minutes to saturate the solution with oxygen. The test was carried out using 6M KOH electrolyte and a three-electrode system, which included a reference electrode (Hg / HgO), a counter electrode (Pt sheet) and a working electrode.
[0107] Supercapacitor performance test: The prepared carbon microspheres were mixed with binder PVDF and carbon black in a mass ratio of 8:1:1 and coated on the electrode sheet to obtain a working electrode. The performance was tested as follows: On a CHI760E electrochemical workstation, a 6M KOH electrolyte and a three-electrode system were used for constant current charge and discharge tests. The electrodes of the three-electrode system included a reference electrode (Hg / HgO), a counter electrode (Pt sheet) and a working electrode. The electrical performance test results are shown in Table 1.
[0108] Table 1
[0109]
[0110] It can be seen from Table 1 that the catalyst and electrode prepared using the solid mesoporous carbon microspheres prepared by the preparation method provided by the present invention as materials have high catalytic effect and capacity and capacity retention rate.
[0111] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention's specification and drawings, or directly or indirectly applied in related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing microspheres, characterized in that: The steps include: S1, mixing phenol and an alkaline catalyst in a solvent to obtain a reaction solution; S2, adding aldehyde to the reaction solution, reacting until turbidity appears, and continuing the reaction for 0 to 90 minutes to obtain a turbid solution; S3, adding silicate to the turbid liquid, and continuing the reaction for 1 to 48 hours; S4, separating and obtaining phenolic resin / silicon dioxide composite particles; S5, carbonizing the phenolic resin / silicon dioxide composite particles and removing silicon dioxide to obtain solid mesoporous carbon microspheres.
2. The preparation method according to claim 1, characterized in that: The phenol is selected from at least one of resorcinol and 3-aminophenol, and the aldehyde is selected from formaldehyde or paraformaldehyde.
3. The preparation method according to claim 1, characterized in that: The alkaline catalyst is selected from at least one of ammonia water, ethylenediamine, ethylamine, diethylamine, triethylamine, hexamethylenetetramine, sodium hydroxide, potassium hydroxide, barium hydroxide and magnesium hydroxide.
4. The preparation method according to claim 1, characterized in that: The solvent is selected from at least one of water, ethanol, methanol, acetone, tetrahydrofuran, methane and chloroform.
5. The preparation method according to claim 1, characterized in that: The silicate is selected from at least one of tetraethyl silicate, tetrapropoxysilane, tetraisopropyl orthosilicate and tetrabutyl silicate.
6. The preparation method according to claim 1, characterized in that: The silicate is added to the turbid solution 10 to 40 minutes after the reaction solution starts to become turbid.
7. The preparation method according to claim 1, characterized in that: The molar ratio of the phenol to the aldehyde is 1:(1-10), and the molar ratio of the alkaline catalyst to the phenol is (1-30):
1.
8. A microsphere prepared by the preparation method according to any one of claims 1 to 7.
9. A noble metal supported catalyst, characterized in that: The microspheres prepared by the preparation method according to any one of claims 1 to 7 are loaded with precious metal compounds.
10. The noble metal supported catalyst according to claim 9, characterized in that: The noble metal compound is selected from at least one of rhodium trichloride, gold trichloride, gold(II) chloride, palladium chloride, chloroauric acid, chloroplatinic acid, potassium hexachloroplatinate, sodium hexachloroplatinate, platinum tetrachloride, platinum acetylacetonate, palladium nitrate, palladium acetate, and tetrachloropalladium ammonium.
11. A silicon dioxide microsphere, characterized in that: The microspheres are obtained by removing the phenolic resin inside the microspheres from the microspheres prepared by the preparation method according to any one of claims 1 to 7.
12. Use of the microspheres as claimed in claim 8 in preparing energy storage devices, adsorbents, catalyst carriers, and drug carriers.
13. Use of the silica microspheres as claimed in claim 11 in preparing battery separators, drug carriers, toothpaste fillers, and silica gel reinforcing agents.